Factors Inhibiting The Utilization of Agricultural Land Management in Improving The Community Economy (Case Study of Embong Village, Embong Satu, Kota Baru, Uram Jaya District) - Faujio Tri Andika; Heni Nopianti; Diyas Widiyarti (Dinasti Research, 2024)
In agriculture in Indonesia, the majority of farmers are rice farmers, which is a type of plant that has been planted for generations and is also used as the main staple of community consumption; if we look closely at the potential of agriculture in Indonesia, it is very strategic for the welfare of the community, especially rural communities or forest fringe communities. In the community of Uram Jaya sub-district, or more precisely, the community of Embong Village, Embong Satu, Kota Baru, they experience a problem where they can only plant rice once a year due to the beliefs that have been held so far by the people there. In addition to the existence of obstacles to the agricultural process by culture and community values and norms, in this village, there are also several disturbances from various aspects ranging from the lack of local government empowerment efforts, lack of knowledge on the creation of new community innovations, and to the state of the community that lacks interest in new things in agriculture. This research aims to determine the community's understanding and ability to use land in the best possible way by knowing the potential inhibiting factors in land utilization and the relationship between government integration with the community in improving agriculture. This study uses qualitative methods with data collection techniques and interviews with the community, the village government, and the community members who participated directly. This research proves that agriculture in Embong, Embong Satu, and Kota Baru villages is experiencing obstacles in its agricultural development due to natural factors, culture, values, norms, and poor community and government relations.